Emergent trends and passing fads in project management research: A scientometric analysis of changes in the field. Issue 1 (January 2015) - Pollack, Julien; Adler, Daniel
Abstract This research uses quantitative techniques to reveal trends in project management related research published between 1962 and 2012. The data set for this research includes 94, 472 unique records sourced from the Scopus and ISI Web of Science databases. The keywords and abstracts that authors have used to describe their work have been analysed in terms of word frequency, rate of change and the co-occurrence of keywords and abstract terms. This data has been used to construct network maps of the field, depicting the relative association between key topics. Comparisons are made between the frequencies of key terms and rapid changes in the ways that terms are used in the literature to identify emergent trends and passing fads. Amongst other findings, this research has revealed evidence to indicate a change in emphasis in project management research from a technical engineering orientation to one which encompasses a broader organisational perspective.